MOCA - Malaysia Online Coding Academy - Muaz Abdullah (International Journal of Informatics and Communication Technology (IJ-ICT), 2015)
Programmer is one of the hottest jobs nowadays. The need of competent programmer is increasing. But the gap between expected skillful software engineer and IT graduate skills is too big. This paper is discussing how an online integrated portal can help producing good software engineers with high programming skill and matching their competencies with job opportunity.